Speciation of Tellurium(VI) in Aqueous Solutions: Identification of Trinuclear Tellurates by 17O, 123Te, and 125Te NMR Spectroscopy - Medvedev, Alexander G.; Savelyev, Oleg Yu; Krut’ko, Dmitry P.; Mikhaylov, Alexey A.; Lev, Ovadia; Prikhodchenko, Petr V. (Molecules (Basel, Switzerland), 2022)
Tellurates have attracted the attention of researchers over the past decade due to their properties and as less toxic forms of tellurium derivatives. However, the speciation of Te(VI) in aqueous solutions has not been comprehensively studied. We present a study of the equilibrium speciation of tellurates in aqueous solutions at a wide pH range, 2.5–15 by 17O, 123Te, and 125Te NMR spectroscopy. The coexistence of monomeric, dimeric, and trimeric oxidotellurate species in chemical equilibrium at a wide pH range has been shown. NMR spectroscopy, DFT computations, and single-crystal X-ray diffraction studies confirmed the formation and coexistence of trimeric tellurate anions with linear and triangular structures. Two cesium tellurates, Cs2[Te4O8(OH)10] and Cs2[Te2O4(OH)6], were isolated from the solution at pH 5.5 and 9.2, respectively, and studied by single-crystal X-ray diffractometry, revealing dimeric and tetrameric tellurate anions in corresponding crystal structures.